Transformasi Digital UMKM Desa Sawangan melalui Implementasi QRIS serta Pemetaan Google Maps - Delinda Yoseatiq Azhar; Irena Zahwa Rakhmaeni; El Rahma Husna; Ailsa Nabilah Ardiningrum; Aulan Darma; Nizar Almas Vatin; Raihanah Arif Ramadhani; Ardi Lutfi Julianto; Wahyu Widi Astuti; Hanif Fadhiil Muammar; Aulia Tri Hutanti; Lorichika Gustinda Larasati (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
This study examines the outcomes of a community-based digital transformation program for Micro, Small, and Medium Enterprises (MSMEs) in Sawangan Village through the implementation of the Quick Response Code Indonesian Standard (QRIS) and the integration of business locations into Google Maps. Prior to the program, most MSMEs relied on cash-based transactions and had limited digital visibility due to the absence of online location mapping. The intervention was implemented across all six hamlets in Sawangan Village and consisted of digital marketing socialization, hands on assistance in QRIS registration, Google Maps business listing, and continuous monitoring and evaluation. The results indicate a significant improvement in MSMEs’ understanding, readiness, and confidence in adopting digital payment systems and utilizing Google Maps as a promotional and accessibility tool. QRIS implementation facilitated faster, safer, and more efficient non-cash transactions, while Google Maps listing enhanced business visibility and consumer accessibility, particularly for customers outside the village area. Despite challenges related to limited digital literacy and technical constraints such as internet connectivity, practical and participatory mentoring proved effective in overcoming these barriers. Overall, the findings demonstrate that sustained, practice-oriented assistance plays a crucial role in accelerating MSME digital adoption, strengthening competitiveness, and supporting sustainable local economic development in rural areas.